Efektivitas Infusa Daun Ruku-ruku (Ocimum tenuiflorum L.) Teknologi Nano sebagai Larvasida Alami terhadap Mortalitas Larva (Aedes aegypti L.) - Fitriyani, Dini; Razak, Abdul; Satria, Rijal; Fransisco Pratama, Sandi (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Dengue fever is caused by the dengue virus which is transmitted through mosquito vectors Aedes aegypti. Vector control is one of the steps to prevent transmission by breaking the vector life cycle using abate. However, its use causes several effects, namely resistance to insects, environmental pollution and insecticide residues. Natural larvicides are an alternative by using plants such as ruku-ruku. Efforts to increase the active ingredient content of ruku-ruku leaves can be done using nanotechnology which has the advantage of increasing the effectiveness and stability of an active ingredient in plants. This research aims to determine the effectiveness of natural larvicide and the best concentration of nanotechnology ruku-ruku leaf infusion on larval mortality Aedes aegypti. This research used a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. The treatments carried out consisted of Control+ (0.01 gram abate), Control- (aquadest), and 3 treatments in the form of ruku-ruku leaf infusion (diluted using nanobubbles) with concentrations of 5%, 15% and 25%. The results of the probit analysis obtained LC50 is 23.829% and the LT50 is 48 hours. The conclusion of this study shows that nanotechnology ruku-ruku leaf infusion is effective on larval mortality Aedes aegypti.